Kepemimpinan Yang Berdaya Dalam Mempersiapkan Dan Mengimplementasikan Perubahan Organisasi - Purba, Roida; Aslami, Nuri (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2023)
This research aims to explore the role of empowered leadership in preparing and implementing organizational change. Qualitative methods were used in this study to gain an in-depth understanding of the experiences and perceptions of leaders and members of the organization regarding the changes that occur. The results showed that empowered leadership has a significant role in facing organizational change. Empowered leaders are able to identify change needs, communicate a clear vision of change, and build trust among organizational members. In addition, empowered leadership is able to motivate and mobilize organizational members, overcome obstacles that arise, and encourage active participation in change. During the change process, empowered leadership also plays an important role in building solid teams, supporting employee learning and development, and creating an organizational culture that supports change and innovation. The findings of this study provide an in-depth understanding of the importance of empowered leadership in preparing for and implementing organizational change. The implications of this research can be used as a guide for organizations in developing and strengthening empowered leadership to face change more effectively and achieve desired change goals. Keywords : Leadership; Empowerment; Change; Organization.